Decreasing Of Oxalate Content in Porang Based on Different Sample Shape, Soaking Time, Temperature, and Soaking Solutions - Sugiarto, Bambang; Sulistyowati, RR Endang; Dewi, Cicilia Tri Marantika; Hendranto, Rahadian Yogi (Eksergi, 2023)
Porang, known for its high oxalate content that poses digestive challenges, served as the underlying problem in this study. The research investigated the impact of immersion conditions on oxalate reduction in porang, both in the form of longitudinal slices and diced pieces, using various soaking media, including vinegar, alcohol, and water, with temperature variations. The study identified that the optimal immersion time for achieving maximum oxalate reduction in longitudinal slices was 150 minutes at 50°C in water, resulting in a 0.00495% decrease. In the case of diced porang, the most significant reduction occurred after 120 minutes at 70°C in alcohol, leading to a 0.0045% decrease. These findings shed light on the influence of porang shape and soaking conditions on oxalate release, with diced porang demonstrating faster oxalate reduction, likely due to its smaller surface area. The study offers valuable insights into effectively reducing oxalate levels in porang, contributing to safer consumption.